Think Amerindia in a poetics of translating Ayvu Rapyta - Ribeiro, João Paulo (Revista de Letras, 2023)
Along with the poetics of translating the text Ayvu Rapyta by León Cadogan (1959), in Mbyá-Guarani, we think about Amerindia, from the Poetics of Relation and the Diverse, concepts by Édouard Glissant ([1990] 2011) as points of reference. On the poetics of translating, it is based on the thought of Henri Meschonnic ([1989] 2006) and from Maria Sílvia Cintra Martins (2022). Our proposal intended to deviate from interpretation, as it established itself attentive to aspects of the diverse within the syntagma provided by the physics of translating, taking into account an extra-world possibility. For a theory of the poem in Amerindia, we reflect on the poem of the world, on the said, having this experience in the poetics of translating Ayvu Rapyta in Amerindia. We chose not to translate some words: tenondé, yvará, kuaa-ra-ra, among others. The language of our proposal is a language of the poetics of the relationship.